Comparing the diagnostic performance of QuantiFERON-TB Gold Plus with QFT-GIT, T-SPOT.TB and TST: a systematic review and meta-analysis - Yu Zhang; Guozhong Zhou; Wei Shi; Weili Shi; Meijun Hu; Defu Kong; Rong Long; Jian He; Nan Chen (BMC Infectious Diseases, 2023)
Abstract Background QuantiFERON-TB Gold Plus (QFT-Plus) is an important test that has emerged in recent years for detecting TB infection. We conducted a review to compare the sensitivity, specificity and positive rate of QFT-Plus with that of QuantiFERON-TB Gold In-Tube (QFT-GIT), T-cell spot of tuberculosis assay (T-SPOT.TB) and Tuberculin test (TST). Methods PubMed and Embase were searched, without language restrictions, from 1 January 2015 to 31 March 2022 using “Mycobacterium tuberculosis Infections” and “QuantiFERON-TB-Plus” as search phrases. We estimated the sensitivity from studies of patients with active tuberculosis, specificity from studies of populations with very low risk of TB exposure, and positive rate from studies of high-risk populations. The methodological quality of the eligible studies was assessed, and a random-effects model meta-analysis was used to determine the risk difference (RD). We assessed the pooled rate by using a random-effects model. This study was registered in PROSPERO (CRD 42021267432). Results Of 3996 studies, 83 were eligible for full-text screening and 41 were included in the meta-analysis. In patients with active TB, the sensitivity of QFT-Plus was compared to that of QFT-GIT and T-SPOT.TB, respectively, and no statistically differences were found. In populations with a very low risk of TB exposure, the specificity of QFT-Plus was compared with that of QFT-GTI and T-SPOT.TB, respectively, and no statistically differences were found. Two studies were eligible to compare the specificity of the QFT-Plus test with that of the TST test, and the pooled RD was 0.12 (95% CI 0.02 to 0.22). In high-risk populations, 18 studies were eligible to compare the positive rate of the QFT-Plus test with that of the QFT-GIT test, and the pooled RD was 0.02 (95% CI 0.01 to 0.03). The positive rate of QFT-Plus was compared with that of T-SPOT.TB and TST groups, and no statistically differences were found. Conclusions The diagnostic performance of QFT-Plus was similar to that of QFT-GIT and T-SPOT.TB, but was slightly more specific than TST.